2011
DOI: 10.1136/sextrans-2011-050125
|View full text |Cite
|
Sign up to set email alerts
|

Educational level and HIV disease progression before and after the introduction of HAART: a cohort study in 989 HIV seroconverters in Spain

Abstract: Results suggest that, despite similar access to HAART, persons with low educational level are at increased risk of HIV disease progression, highlighting the impact of social inequities on health. The availability of more effective treatments over time will strengthen the protective effect of higher education on the development of AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…The majority of the participants in our study were uneducated, which is similar to the findings in the Peshawar study and those reported from other parts of the world (7,14). Level of education is an important factor as it determines knowledge about the disease.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The majority of the participants in our study were uneducated, which is similar to the findings in the Peshawar study and those reported from other parts of the world (7,14). Level of education is an important factor as it determines knowledge about the disease.…”
Section: Discussionsupporting
confidence: 79%
“…A study conducted in a postgraduate college of Rahim-Yar Khan, Pakistan reported that knowledge about HIV and AIDS was greater in students with 13 and 14 years of education as compared to those with 11 and 12 years (15). A multicentre study in Spain of an HIV-positive cohort reported that a greater proportion of the cohort had a low educational level (14). Less educated people were found at increased risk of disease progression compared to more highly educated people and the risk of death was lower among those with a higher education level (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that age, gender, transmission category, educational level, marital status, and CD4 + T-cell count [4], [9], [10], [11], [12] might be markers for differences in access to treatment, adherence, or disease severity at diagnosis, ultimately leading to disparities in survival. Moreover, it would also be meaningful work to find out factors [13] which may be associated with progression to AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…We end with the interaction between education and HIV progression in a Spanish cohort,12 and missed diagnosis of Kaposi's sarcoma in a man with high CD4 count and low viral load 13…”
mentioning
confidence: 99%